The Influence of Using Multimedia-Based Microsoft Power Point on Class VI Science Learning Outcomes at SDN 03 Alai - ajis, yovie As Sami; Zuliarni, Zuliarni; Bentri, Alwen; Rahmi, Ulfia (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The use of learning media is one way to develop education, the influence of media use provides results that show the extent to which the success of learning media has an impact on education so that the supporting factors and disadvantages will be known. The learning media examined in this research is Microsoft Powerpoint or PPT learning media. This research aims to determine the significant influence of using multimedia-based Microsoft Power Point media on the science learning outcomes of class VI students at SDN 03 Alai Padang. The research results show that the average score obtained from the learning outcomes of students who use Microsoft Power Point-based multimedia (experimental class) is higher. This is in accordance with the average student learning outcomes in the experimental class of 75.17, which is higher than the control class, namely 63.92. Based on the results of the t test, the calculated t is 2.083 and the t table with a significance level of 0.05 is 2.004. So if we compare the numbers 2.083 > 2.004 then it can be interpreted that H1 is accepted. So it can be concluded that the use of multimedia-based Microsoft Power Point has a significant effect on the science learning outcomes of class VI students at SDN 03 Alai.